2020
DOI: 10.4236/fns.2020.118056
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Protein Content and Dietary Fibre in a Composite Flour Blend Containing Rice (<i>Oryza sativa</i>), Sorghum [<i>Sorghum bicolor</i> (L.) Moench] and Bamboo (<i>Yushania alpine</i>) Shoots

Abstract: Initiatives on tackling food insecurity among global emerging economies are being focused on enriching native staple foods with locally available nutritious underutilized crops. The objective of this study was to optimize protein content and dietary fibre in rice (Oryza sativa) flour using Sorghum (Sorghum bicolor L.) and Bamboo shoots (Yushania alpina). An extreme vertices How to cite this paper: Wanjala, W.N., Mary, O. and Symon, M. (2020) Optimization of Protein Content and Dietary Fibre in a Composite Flou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…A factorial experiment design with three variables: Feed mixture composition of rice flour, sorghum, and bamboo shoot flour (BSF) (100:0:0, 70:30:0, 50:27:23, 60:30:10, and 55:35:15), water addition rate (15, 20 and 25 kg/h) and feed rate (1,800 and 2,100 kg/h) were adopted for the study. Feed compositions were modified composites established to optimize protein content, dietary fiber, and minerals according to a study by Wanjala et al., (2020). Feed rate levels and water to be added were established during the extrusion process pre‐trials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A factorial experiment design with three variables: Feed mixture composition of rice flour, sorghum, and bamboo shoot flour (BSF) (100:0:0, 70:30:0, 50:27:23, 60:30:10, and 55:35:15), water addition rate (15, 20 and 25 kg/h) and feed rate (1,800 and 2,100 kg/h) were adopted for the study. Feed compositions were modified composites established to optimize protein content, dietary fiber, and minerals according to a study by Wanjala et al., (2020). Feed rate levels and water to be added were established during the extrusion process pre‐trials.…”
Section: Methodsmentioning
confidence: 99%
“…The shoots were then dried on a fire stand to a moisture content of about 10%. Rice and sorghum had initial moisture level of 13.6% and 10.5%, respectively, as reported in Wanjala et al, (2020). All the ingredients: Rice, Sorghum and bamboo shoots were milled using a hammer mill and the flour passed through a sieve with average pore size of 800 µm.…”
Section: Methodsmentioning
confidence: 99%
“…Edible shoots of Yushania alpina (Alpine bamboo) were collected from Mt. Elgon National Reserve, Bungoma County, Kenya and prepared according to Wanjala et al [16]. The young culms were harvested at 4 -6 weeks after the onset of April-May, 2021 rainfall.…”
Section: Methodsmentioning
confidence: 99%
“…The wide array of both nutritional and health benefits based on the many studies has attracted global interest in the exploration of the juvenile bamboo shoots as a novel source of nutrition. Apart from consumption as a vegetable, studies that incorporated BS into other products for value addition and product development have emerged [11,[13][14][15][16]. Various acceptable products from these investigations include; fortified cookies and biscuits, yeast, extruded ready-to-eat snacks, cupcakes and purees [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have evaluated PD when CF was proposed, the results remain scarce and variable. Wanjala et al (2020) reported an increase in protein content (from 6.47% to 10.70%) when 30% of rice flour was replaced with 10% sorghum and 20% bamboo shoots. However, PD decreased from 85.61% (rice flour) to 65.65% (CF).…”
Section: Composition Aspectsmentioning
confidence: 99%